The first option and the third one
F(x) = 2 x - 5
15 = 2 x - 5
2 x - 5 = 15
2 x = 15 + 5
2 x = 20
x = 20 / 2
x = 10
hope this helps!
Answer:
4a³+3a-3
Step-by-step explanation:
You can solve this by combining like terms. Add the numbers with the correct exponents together.
-a³+5a³
4a-a
Thus, the answer is
4a³+3a-3
Answer:
hope that helps
Step-by-step explanation:
Factoring p2-14p-24
The first term is, p2 its coefficient is 1 .
The middle term is, -14p its coefficient is -14 .
The last term, "the constant", is -24
Step-1 : Multiply the coefficient of the first term by the constant 1 • -24 = -24
Step-2 : Find two factors of -24 whose sum equals the coefficient of the middle term, which is -14 .
-24 + 1 = -23
-12 + 2 = -10
-8 + 3 = -5
-6 + 4 = -2
-4 + 6 = 2
-3 + 8 = 5
-2 + 12 = 10
-1 + 24 = 23